Thrombin activatable fibrinolysis inhibitor - Declerck, P. J. (Hämostaseologie, 2011)
Thrombin activatable fibrinolysis inhibitor (TAFI) was discovered two decades ago as a consequence of the identification of an unstable carboxypeptidase (CPU), which was formed upon thrombin activation of the respective pro-enzyme (proCPU). The antifibrinolytic function of the activated form (TAFIa, CPU) is directly linked to its capacity to remove C-terminal lysines from the surface of the fibrin clot. No endogenous inhibitors have been identified, but TAFIa activity is regulated by its intrinsic temperature-dependent instability with a half-life of 8 to 15 min at 37 °C. A variety of studies have demonstrated a role for TAFI/TAFIa in venous and arterial diseases. In addition, a role in inflammation and cell migration has been shown. Since an elevated level of TAFIa it is a potential risk factor for thrombotic disorders, many inhibitors, both at the level of activation or at the level of activity, have been developed and were proven to exhibit a profibrinolytic effect in animal models. Pharmacologically active inhibitors of the TAFI/TAFIa system may open new ways for the prevention of thrombotic diseases or for the establishment of adjunctive treatments during thrombolytic therapy.
Keywords: Thrombin activatable fibrinolysis inhibitor; TAFI; proCPU; fibrinolysis